2017
DOI: 10.9790/0853-1601115660
|View full text |Cite
|
Sign up to set email alerts
|

A Histopathological Study of Endometrium in Infertility

Abstract: Abstract:Infertility is defined as inability of couple to achieve conception after one year of unprotected coitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
3
1
0
Order By: Relevance
“…In the present study, a luteal phase defect was noted in 3 of the 75 cases (4%) studied. This is similar to that noted by Murmuet al 6 who reported luteal phase defect in 8.2 % of the 79 cases studied. This is the present study accounted for 1 of the 58 (3.5 %) cases with primary infertility and 2 of the 17 (5.8%) cases with secondary infertility.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, a luteal phase defect was noted in 3 of the 75 cases (4%) studied. This is similar to that noted by Murmuet al 6 who reported luteal phase defect in 8.2 % of the 79 cases studied. This is the present study accounted for 1 of the 58 (3.5 %) cases with primary infertility and 2 of the 17 (5.8%) cases with secondary infertility.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, endometrial hyperplasia accounted for 4% of the 75 cases. This is similar to the observations of Murmu et al 6 (2.74%), Sabharwal et al 12 (2.66%), Shastrabudhe et al 13 (4.4%), and Sharma et al 14 (6.0%). Ahmed et al 10 from Bangladesh who found a slightly higher incidence of 10.7%, analyzed data from various countries and found this feature to be lower in India compared to Pakistan and Nigeria where incidence was as high as 14% and 20% respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most common age group of infertility was from 21 years to 30 years which correlated with the studies done by 10,11,13,14,16,17 Secretory phase endometrium means that the women is ovulating and there are good chances of conception in subsequent cycles. However, inspite of ovulatory endometrium defect may be present somewhere else, it can be due to luteal phase defect and depletion of glycogen that results in inadequate preparation of endometrium at the time of implantation and henceforth leading to infertility.…”
Section: Age Distributionsupporting
confidence: 54%